2022
DOI: 10.1200/jco.2022.40.4_suppl.059
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of survival trends, clinical, and molecular characteristics of patients with early-onset colorectal cancer (EOCRC).

Abstract: 59 Background: Over the last decades the incidence of EOCRC (age 50 or less) has dramatically increased, and so has the scientific interest in this field, given that clinical and molecular characteristics in these patients are not well understood, and may be critical to identify prognostic factors. Methods: We conducted a retrospective analysis of 554 patients with metastatic colorectal cancer (mCRC), analyzing the PFS and OS of 68 (12.25%) patients with EOCRC, as well as their clinical and molecular characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nevertheless, in clinical practice, the age at diagnosis might influence physicians’ decision-making. Considering that younger patients tend to have better performance status and fewer comorbidities, the evidence shows that EOCRC is likely to receive more aggressive treatment, with conflicting data on the potential prognostic advantages [ 81 , 121 , 122 ]. An American cohort study involving 13,102 EOCRC patients (18 to 49 years) and 37,007 LOCRC patients (65 to 75 years) treated with curative-intent surgery and adjuvant chemotherapy reported that Stage IV CRC patients younger than 40 tended to undergo more systemic therapy and radiation with minimal survival gain (relative risk 0.84; 95% CI 0.79–0.90) [ 81 ].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in clinical practice, the age at diagnosis might influence physicians’ decision-making. Considering that younger patients tend to have better performance status and fewer comorbidities, the evidence shows that EOCRC is likely to receive more aggressive treatment, with conflicting data on the potential prognostic advantages [ 81 , 121 , 122 ]. An American cohort study involving 13,102 EOCRC patients (18 to 49 years) and 37,007 LOCRC patients (65 to 75 years) treated with curative-intent surgery and adjuvant chemotherapy reported that Stage IV CRC patients younger than 40 tended to undergo more systemic therapy and radiation with minimal survival gain (relative risk 0.84; 95% CI 0.79–0.90) [ 81 ].…”
Section: Treatmentmentioning
confidence: 99%
“…A recent analysis of 554 mCRC patients showed that EOCRC patients (≤50 years) received more lines of chemotherapy (2.94 vs. 2.38, p = 0.027) and underwent more surgeries (2.42 vs. 1.24; p < 0.001) than their older counterparts. Furthermore, the younger cohort demonstrated better survival in first-line treatment (mPFS 16.2 vs. 11.3 months, p = 0.042; mOS 121.5 vs. 58.1 months, p = 0.011) [ 122 ]. Other data suggested no significant difference in the recurrence rate in radically resected Stage III and IV young patients (27.5% vs. 27.9%, p = 0.325), even though they had more advanced stages at diagnosis (55.6% vs. 47.9%, p = 0.001) and worse cancer-specific survival (81.2% vs. 87.8%, p < 0.001) [ 123 ].…”
Section: Treatmentmentioning
confidence: 99%